The Most Influential Factors on The Risk Cost Estimation Process of Implementing Bim 5d in Quantity Take-Off for Green Retrofitting of High-Rise Buildings - Dewi, Febrianti Silviana; Latief, Yusuf; Kussumardianadewi, Bernadette Detty (UI Scholars Hub, 2024)
Green retrofitting aims to guide buildings toward sustainable practices, reducing carbon emissions associated with building operations and construction. This study explores the application of Building Information Modeling (BIM) 5D Quantity Take-Off (QTO) to existing high-rise buildings, focusing on components that enhance the performance of environmentally friendly structures and project management. This research identifies the factors influencing the cost estimation process and examines the risks across various phases, activities, outputs, and utilization of BIM 5D in cost estimation. The study highlights the most influential factors in implementing green retrofitting for high-rise buildings using structured interviews, questionnaires, and expert validation. The analysis demonstrates that BIM 5D QTO significantly impacts the risk associated with cost estimation in green retrofitting processes. The study ranks the criteria based on respondent feedback by employing Relative Importance Index (RII) analysis. The statistical analysis identifies key factors affecting the risk of cost estimation in BIM QTO for green retrofitting of high-rise buildings. These factors include evaluating specifications, defining acceptance criteria, decomposing the high-level Work Breakdown Structure (WBS), inputting sizes and specifications of each work component into the 3D model, integrating scheduling into the 3D model, and establishing a BIM Execution Plan.